The role of visceral adipose tissue in insulin resistance and metabolic syndrome (Research, Society and Development, 2026)
Obesity is one of the major challenges in contemporary public health, being strongly associated with the development of metabolic disorders, especially insulin resistance and metabolic syndrome. Scientific evidence suggests that the accumulation of visceral adipose tissue plays a central role in the pathophysiology of these conditions, acting as a metabolically active endocrine organ. This study aimed to analyze the role of visceral adipose tissue in the development of insulin resistance and metabolic syndrome, highlighting the main pathophysiological mechanisms involved. It is a qualitative marrative literature review based on scientific articles published in the last tem Years in the PubMed, SciELO, LILACS, and Google Scholar databases, in Portuguese and English. The results show that excesso visceral adiposity promotes increased release of free fatty acids, na imbalance in adipokine secretion, chronic low-grade inflammation, and oxidative stress-mechanismsthat compromisse insulin signaling and contribute to metabolic dysfunction. A Strong association was also observed between visceral obesity and a higher prevalence of componentes of metabolic syndrome, increasing cardiovascular risk and the development of type 2 diabetes mellitus. It is concluded that visceral adipose tissue plays a determining role in the genesis of insulin resistance and metabolic syndrome, highlighting the importance of multidisciplinar therapeutic strategies aimed at reducing central adiposity and promoting metabolic health.